Students and political practice in Algeria Creuser dans les racines et les Paris - ghellab, rabie; mouldi, achour (Journal of Social Sciences and Humanities, 2021)
This study addresses one of the main topics namely" students and political practice in Algeria socio historical study. It is an attempt to find reasons for neglecting University students as a social group of community groups from the political scene. This topic is controversial and of considerable abate among Arab scholars. It identifies obstacles and reasons that led to the reluctance of University student of politics .In the Algerian society, the participation in political life decreases from one occasion to another, Young people seem to boycott elections. Statistics published by the official institutions governing the electoral process or some institutions of civil society show that young people do not give great importance to political practices and especially the political reluctance among many student because of the social and political conditions, marginalization unemployment and political speeches which carries intimidation and enticement. This led the student lives a kind of blur and political disenfranchisement experienced by the country as a result of blundering and refused to change policy by the political system. This study aims atexaminating the causes of the exclusion of student as an active member of the community in building and developing the nation, understand the driving force of political development which led to the departure of students demanding change of the corrupt system in the mobility of people since 22 February to this day, And the emergence of political awareness as a result of its peacefulness and civilization.